Comparative study on karyotypes of three Mastacembelus species (Synbranchiformes: Mastacembelidae) from Thailand - WATCHARIN SEREE; WEERAYUTH SUPIWONG; GETLEKLA NUNTAPORN; SUKHONTHIP DITCHAROEN; NATTHASUDA DONBUNDIT; KRIENGKRAI SEETAPAN; SAMPAN TONGNUNUI; SITTHISAK JUNTHARAT; ALONGKLOD TANOMTONG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Seree W, Supiwong W, Nuntaporn G, Ditcharoen S, Donbundit N, Seetapan K, Tongnunui S, Juntharat S, Tanomtong A. 2025. Comparative study on karyotypes of three Mastacembelus species (Synbranchiformes: Mastacembelidae) from Thailand. Biodiversitas 26: 246-254. Karyotype study or chromosomal study is necessary for some cases of fish taxonomy. The chromosomes of three Mastacembelus species named Zig-zag eel or Mastacembelus armatus, Fire eel or Mastacembelus erythrotaenia, and Tire track eel or Mastacembelus favus using conventional Giemsa staining and Ag-Nucleolar Organizer Region (NOR) banding techniques were investigated. The results indicated that conserved diploid number (2n) of 48 and the fundamental number or chromosome arm number (NF) as 62 for all analyzed species of male and female specimens were revealed, although varying in their karyotype structures were observed. Karyotypes of three species are as follows: 12m+2sm+2a+32t, 10m+6sm+32t, and 8m+6sm+34t in M. armatus, M. erythrotaenia, and M. favus, respectively. In each species, positive Ag-NOR markers were differentially observed adjacent to telomeric and/or sub-telomeric regions (telomeric NORs) of metacentric or submetacentric chromosomes. In M. armatus, NOR locations are at the long arm of the first metacentric chromosome pair, while in M. favus and M. erythrotaenia, NOR locations are at the short arm of the first submetacentric chromosome and the first metacentric chromosome pairs, respectively. The findings show that Mastacembelus species, despite having a conserved diploid number, differ remarkably in the patterns of Nucleolar Organizer Regions (NORs) in their karyotypes. These species-specific patterns can be useful in further characterizing and identifying different species and investigating the evolutionary mechanisms driving the evolution of these fish karyotypes.